1 2 1 2
1 7 9

:

  1. #1

    Jul 2011
    -
    716

    .
    .
    .

    H2(g 2e- + 2H+(aq) E =


    2e- + 2H+(aq) H2(g E =

    H+I ( 1/). 25 .

    ɡ .
    :
    ( E ) = .


  2. #2

    Jul 2011
    -
    716

    :

    1 :
    (1 /) ( 25 ) (0.76 ) .
    .
    2e- + Zn+2 Zn
    H2 2e- + 2H+
    = 0.76 .
    ( E ) = .
    ( E ) =
    0.76 = - E
    = -0.76
    Zn  2e- + Zn+2 E = - 0.76
    . .
    .
    2e- + Zn+2  Zn E =+ 0.76


  3. #3

    Jul 2011
    -
    716

    :

    2 :
    ( 1 / )
    ( 25 ) (0,34 ) .
    .
    Cu+2 + 2e- Cu
    H2 2H+ + 2e-
    = 0.34 .
    ( E ) = .
    ( E ) =
    0.34 = E -
    = +0.34 .
    Cu 2e- + Cu+2 E- = +0.34
    . .
    .
    2e- + Cu+2  Cu E = -0.34
    :
    .
    .

    (1): PbSO4 ( 1 / ). ɡ 0.13 .
    1- .
    2- .
    3- .
    4- Pb+2 .
    5- .
    6- .
    7- .
    8- ա .


    (2): : 1- . 2- .
    :
    = 0.40 E Cd+2 + 2e- Cd
    = + 0.80 E Ag + e- Ag


  4. #4

    Aug 2011
    -
    2,559

    :

    ..

  5. #5

    Aug 2011
    -
    3,024

    :






  6. #6

    Aug 2011
    2,844

    :

    Thank you so much
    refresh

    refresh


  7. #7

    Jul 2011
    -
    15,555

    :








1 2 1 2

: 1 (0 1 )

, ,